Effectiveness on C Flaws Checking and Removal - Inacio, Joao; Medeiros, Iberia (2022 52nd Annual IEEE/IFIP International Conference on Dependable Systems and Networks - Supplemental Volume (DSN-S), 2022)
The use of software daily has become inevitable nowadays. Almost all everyday tools and the most different areas (e.g., medicine or telecommunications) are dependent on software. The C programming language is one of the most used languages for software development, such as operating systems, drivers, embedded systems, and industrial products. Even with the appearance of new languages, it remains one of the most used [1] . At the same time, C lacks verification mechanisms, like array boundaries, leaving the entire responsibility to the developer for the correct management of memory and resources. These weaknesses are at the root of buffer overflows (BO) vulnerabilities, which range the first place in the CWE's top 25 of the most dangerous weaknesses [2] . The exploitation of BO when existing in critical safety systems, such as railways and autonomous cars, can have catastrophic effects for manufacturers or endanger human lives.